Extension Management in Drylands under Climate Change Scenarios - Singh, Y V; Kumawat, R N (Annals of Arid Zone, 2016)
In drylands of arid and semi-arid regions extension management is challenging task under climate change scenario. The brief accounts on technology development and dissemination since 1928 alongwith constraint issues for transferring like; technological, economical, socio-physiological, infrastructure at managerial, communicational, political are described. Professionalism particularly in dryland areas need more attention, where in parameter like work under complex and fluid situation, diagnose farmers’ problem efficiently, learn from farmers, communicate efficiently and work with group of farmers. It can be enhanced through education and training where KVK have to play an important role to promote secondary agriculture for livelihood security with the cooperation of line departments. This may help in increasing the production and productivity of dryland areas